Alpine radish rhizosphere microbiome assembly and metabolic adaptation under PBAT/PLA humic acid biodegradable mulch films - Zhong, Jian; Li, Ju; Liao, Jichao; Ma, Yanqin; Li, Zhi; Yang, Liang; Chang, Wei; Miao, Mingjun (Frontiers in Microbiology, 2025)
IntroductionAlpine agroecosystems present unique crop production challenges due to extreme environmental conditions, where rhizosphere microbiomes significantly influence plant adaptation.MethodsTo investigate mulch-induced microbial changes in high-altitude agriculture, this study analyzed a radish field in China using SMRT sequencing (16S rRNA/ITS) and metagenomics, comparing PBAT/PLA biodegradable films with/without humic acid (HA) at varying thicknesses.ResultsResults demonstrated that radish cultivation selectively enriched Proteobacteria and Acidobacteriota while depleting Chloroflexi and Actinobacteria, with fungal communities shifting from Basidiomycota-to Ascomycota-dominance. Notably, HA-amended mulches enhanced bacterial diversity and specifically promoted polymer-degrading microbes (Chitinophagaceae, Candidatus_Udaeobacter, Chaetomiaceae). Metagenomic profiling revealed thickness-dependent increases in functional genes related to carbohydrate and amino acid metabolism in HA-treated soils.ConclusionThese findings advance our understanding of how biodegradable mulch formulations can be optimized to enhance microbial ecosystem services in alpine farming systems.